Frontier Analysis: A State-of-the-Art Review and Meta-Analysis. (May 2016) - Assaf, A. George; Josiassen, Alexander
This article presents a comprehensive review of frontier studies in the tourism literature. We discuss the main advantages and disadvantages of the various frontier approaches, in particular, the nonparametric and parametric frontier approaches. The study further differentiates between micro and macro applications of these approaches, summarizing and critically reviewing the characteristics of the existing studies. We also conduct a meta-analysis to create an overview of the efficiency results of frontier applications. This allows for an investigation of the impact of frontier methodology on tourism research. The present review also highlights the limitations of existing studies and suggests an agenda for future research.